IKLIM ORGANISASI, KETERAMPILAN MANAJERIAL DAN KINERJA KEPALA SMK DI KOTA PADANG - Ika Yuanita; Nurhayati Nurhayati (Politeknik Negeri Padang, 2018)
The objective of research is to describe organizational climate and managerial skills, and principal performance of SMK in Padang City in order to improve educational quality of vocational unit.Research designed by descriptive-explanatory with population in this study are teachers of the public and private SMK in academic year 2016/2017. the population are 1,628 teachers with stratified random sampling technique (with 94 samples). Empirical finding shows that a few SMK principal carry out supervision with actions to all education units; ineffective school organizational structure;, school team coordination has not been created well, and the absence of school personnel performance and evaluation within a certain period. That also influenced by the climate of vocational organizations, both physical buildings and learning technology facilities. In addition, the education level of the vocational school principals about 51.2% graduated from the bachelor's degree, which determines managerial ability to manage school in a professional manner.